Performance evaluation of different configurations of system with DSTATCOM using proposed Icos⁡ϕ technique - Atma Ram; Parsh Ram Sharma; Rajesh Kumar Ahuja (Institute of Advanced Engineering and Science, 2022)
The proposed Icos⁡ϕ control technique has been applied for power quality improvement using different configurations of system with distribution static compensator (DSTATCOM). Modeling, design and control of DSTATCOM are analysed in detial. Three phase reference current are extracted with this technique. The proposed technique has been used for power factor enhancement, voltage regulation, harmonic suppression and load balancing under dynamic condition with non-linear load. The proposed control is very effective for three different configurations of system with DSTATCOM for power quality improvement. Results for each configuration of system with DSTATCOM are simulated using MATLAB/Simulink sim power tool box. For teaching the power quality course, these can also be helpful.